The impact of the brain drain process on Romania: Possible solutions in order to increase resilience - George-Cristian Gavriloaia (CES Working Papers, 2020)
The paper presents the implications of the brain drain phenomenon in Romania, focusing on possible solutions at European, national and local level. The consequences of the brain drain phenomenon as well as the magnitude of the problem in Romania were analysed based on a quality methodology, namely the secondary analysis of statistical data, all in correlation with other concepts such as trust, vulnerability and resilience. Although there are still no analytical indicators to accurately measure them, the conclusions and recommendations that have been made showed that a bottom-up approach to highlighting the solutions already implemented can be seen as a future model for brain drain analysis.
Keywords: 330; brain drain; increase resilience; cohesion policies